There is More to the Story than Skipping School - Loz J. Hennessy (Journal of Extreme Anthropology)
This article offers a reflective exploration of the storied experiences of young climate strikers in Bristol through a narrative inquiry approach. In-depth analysis of the narratives of the young people collected at two distinct timepoints illustrates the complexity of young people’s stories of activism to develop a localised sub-narrative. Before the covid-19 pandemic, young people’s climate activism was at a high with the movement known as Youth Strike 4 Climate (YS4C) or Fridays For Future (FFF). The wave of young people’s climate activism was sustained by a powerful metanarrative (Han and Ahn 2020). This study explores the narrative accounts of three youth activists in Bristol to draw out distinct components of the local sub-narrative of the YS4C movement. The data is collected though in-depth narrative interviews in 2020 and follow-up interviews in 2023. The narrative approach taken in this article views the process of telling and re-telling stories as a collaborative meaning-making process (Clandinin and Connelly 2000); by reflecting back on their own earlier words, the young people are brought into the research process and centred as co-producers of knowledge. The study finds that their accounts are action-oriented, justice-driven and community-focussed. The narratives reveal how young activists cast themselves as protagonists and thereby enact political agency. Striking as a tactic is explored from the perspective of a post-covid world. The article suggests that the end of the strikes locally does not signify the end of the movement.